2022
DOI: 10.1038/s41598-022-09133-9
|View full text |Cite|
|
Sign up to set email alerts
|

Enoxaparin augments alpha-1-antitrypsin inhibition of TMPRSS2, a promising drug combination against COVID-19

Abstract: The cell surface serine protease Transmembrane Protease 2 (TMPRSS2) is required to cleave the spike protein of SARS-CoV-2 for viral entry into cells. We determined whether negatively-charged heparin enhanced TMPRSS2 inhibition by alpha-1-antitrypsin (AAT). TMPRSS2 activity was determined in HEK293T cells overexpressing TMPRSS2. We quantified infection of primary human airway epithelial cells (hAEc) with human coronavirus 229E (HCoV-229E) by immunostaining for the nucleocapsid protein and by the plaque assay. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…Mechanistically, this infers that the expulsion of the AT RCL, rather than the formation of the ternary complex between protease, antiprotease, and its activator, is responsible for this effect. A recent study described a reduction of electrostatic repulsions between the serpin α 1 AT and the low molecular weight heparin (LMWH) enoxaparin, 85 which might also contribute to the activation of AT. Heparin or LMWH are administered as the standard of care in the majority of COVID‐19 patients at daily intravenous doses of several thousand international units (IU), while FPX is administered at 2.5 mg, respectively 74,80,86 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this infers that the expulsion of the AT RCL, rather than the formation of the ternary complex between protease, antiprotease, and its activator, is responsible for this effect. A recent study described a reduction of electrostatic repulsions between the serpin α 1 AT and the low molecular weight heparin (LMWH) enoxaparin, 85 which might also contribute to the activation of AT. Heparin or LMWH are administered as the standard of care in the majority of COVID‐19 patients at daily intravenous doses of several thousand international units (IU), while FPX is administered at 2.5 mg, respectively 74,80,86 .…”
Section: Discussionmentioning
confidence: 99%
“…Because AAT is a potent serpin, it has the potential to inhibit both TMPRSS2 and SARS-CoV-2 infection. Indeed, in HEK293T cells engineered to overexpress TMPRSS2, physiologic concentrations of AAT potently inhibited TMPRSS2 activity [ 86 , 87 ]. Ritzmann et al [ 88 ] showed in both two-dimensional submerged airway epithelial cells and three-dimensional airway epithelial organoid cultures that physiologic concentrations of AAT (1 and 5 mg/ml) significantly inhibited TMPRSS2 activity and decreased intracellular burden of SARS-CoV-2 [ 88 ].…”
Section: Aat Inhibits Tmprss2 and Sars-cov-2 Entry Into Cellsmentioning
confidence: 99%
“…It is important to point out that AAT interacts with cytokines, free heme, heparins, lipoproteins, and other substances (Bergin et al, 2010;Karnaukhova et al, 2012). For example, AAT shows better anti-elastase activity in complex with high-density lipoprotein or heparin than by itself (Houghton et al, 2010;Lechowicz et al, 2020;Bai et al, 2022). AAT also interacts with chemoattractants, such as IL-8 and leukotriene B4 (LTB4), and thus modulates neutrophil adhesion and chemotaxis (Mcelvaney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%